The Effect of Contract Value on the Performance of the Security Unit (Security Guard) of PT. Multi Daya Utama - BY, Ismawan; Setiawan, H. Awan; Ramdani, Dani (Jurnal Ilmiah Sumber Daya Manusia, 2026)
Objective: This study aims to analyze the influence of contract value on the performance of security guards at PT Multi Daya Utama, a Security Services Business Entity (BUJP). The study employs a quantitative associative approach using simple linear regression analysis. Data were collected through questionnaires distributed to 63 security personnel respondents. The analysis indicates that contract value has a positive and significant influence on security guard performance, with a significance value of 0.000 < 0.05. The coefficient of determination (R2) shows that the contract value variable contributes 71.41% to the fluctuations in personnel performance, while the remaining 28.59% is influenced by other factors. Implications: Fulfilling financial components and facilities within cooperation contracts is a determinant factor in enhancing the professionalism and discipline of members in the field, as well as a vital instrument in realizing the professional development of security guards in accordance with the mandate of Perpol No. 4 of 2020.